ANALYSIS OF SALES VOLUME THROUGH THE UTILIZATION OF SHOPEE AND TIKTOK SHOP - Adzra Ashila (Journal Business Administration: Entrepreneurship and Creative Industry, 2024)
The development of technology and telecommunications caused by globalization requires entrepreneurs to change their marketing strategies in order to keep up with the changes. The marketing strategy in question is digital marketing. Digital marketing techniques include many things, such as content marketing, social media marketing, email marketing, and search engine optimization (SEO). This research aims to determine the effect of Shopee and TikTok Shop on sales volume in a business. This research uses descriptive qualitative methods, the data collection techniques used are interviews, observation, and documentation, researchers want to analyze how the sales volume of Denisa Fashion Shop when utilizing digital marketing strategies with Shopee and TikTok Shop as the media. The results of this study indicate that the use of these two applications provides positive results because it can increase sales volume followed by increased business profits.